SOSIALISASI PROGRAM KABUPATEN/KOTA SEHAT DI FORUM KOTA SEHAT TEGALLAYANG, CATURHARJO, KAPANEWON PANDAK, BANTUL - Kasjono, Heru Subaris; Rubaya, Agus Kharmayana; Kusumastuti, Yuni; Yamtana, Yamtana; Sintawati, Ratna Etika (LPPM Institut Pendidikan Nusantara Global, 2024)
Tegallayang, Caturharjo, Kapanewon Pandak, Bantul Regency, Special Region of Yogyakarta, is one of the designated locations for the Healthy District or City (Kabupaten atau Kota Sehat, KKS) assessment in Bantul in 2025. To achieve the objectives of this program, the local government must establish a forum focused on empowering community cadres. However, not all regions have effectively implemented the Healthy District or City program. Challenges include the lack of outreach and socialization by the government, resulting in limited public awareness of the program, as well as inadequate cross-sectoral collaboration. This community engagement activity aims to enhance knowledge about the Healthy District or City initiative and provide guidance for creating residential areas that meet health indicators. The methods employed include delivering material using PowerPoint presentations and LCD projectors, targeting the Healthy District or City forum groups in Kapanewon Pandak, Bantul